East Indian women wearing traditional Lugra - Mumbai Archive Project Team (Jio Institute, 2024)
On this special day, East Indian women wear their traditional attire, a nine-yard sari worn in the Maharashtrian kashta style, known as the Sonkari Lugra. The Lugra is distinctive for its pink or red colour and intricate embroidery along its border.